CBP/p300 as a co-factor for the Microphthalmia transcription factor. - Sato, S; Roberts, K; Gambino, G; Cook, A; Kouzarides, T; Goding, C (1997)
The Microphthalmia basic-Helix-Loop-Helix-Leucine Zipper (bHLH-LZ) transcription factor (Mi) plays a crucial role in the genesis of melanocytes; mice deficient for a functional (Microphthalmia) gene product lack all pigment cells. We show here that the Mi activation domain resides N-terminal to the DNA-binding domain and that as little as 18 amino acids are sufficient to mediate transcription activation. The minimal activation region of Mi is highly conserved in the related transcription factor TFE3 and is predicted to adopt an amphipathic alpha-helical conformation. This region of Mi is also highly conserved with a region of E1A known to be essential for binding the CBP/p300 transcription cofactor. Consistent with these observations, the Mi activation domain can interact in vitro with CBP specifically through a region of CBP required for complex formation with E1A, P/CAF and c-Fos, and anti p300 antibodies can co-immunoprecipitate Mi from both melanocyte and melanoma cell lines. In addition, co-transfection of a vector expressing CBP2 (aas 1621-1891) fused to the VP16 activation domain potentiated the ability of Mi to activate transcription, confirming the significance of the CBP-Mi interaction observed in vitro. These data suggest that transcription activation by Mi is achieved at least in part by recruitment of CBP. The parallels between transcription regulation by Microphthalmia in melanocytes and MyoD in muscle cells are discussed.